Preparation method of grinding aid for Sc / O doped sulfide solid electrolyte

Through the preparation method of the abrasive agent for Sc/O doped sulfide solid electrolyte, the microstructure of the Li6PS5Cl type sulfide solid electrolyte is improved, the problems of its sensitivity to moisture and poor interface compatibility are solved, and the conductivity and safety of the electrolyte are improved.

CN119528090AActive Publication Date: 2025-02-28TIANNENG BATTERY GROUP

Patent Information

Application Number
CN202510106270.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-02-28
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

Li6PS5Cl type sulfide solid electrolyte is sensitive to moisture in the air and has poor interface compatibility, resulting in uneven deposition of lithium ions and easy formation of lithium dendrites, affecting the stability and safety of the battery.

Method used

Using the preparation method of a grinding aid for Sc/O doped sulfide solid electrolyte, the microstructure of the electrolyte of electrolyte is improved by mixing ethanolamine thioglycolate, 2-vinyl-5,5-dimethyl-1,3,2-dioxoborane, 1-allyl-3-ethylimidazole hexafluorophosphate and potassium ethanol in a solvent to form a grinding aid, and added to the Sc/O doped sulfide solid electrolyte, the microstructure of the electrolyte is improved by ball milling and heat treatment.

Benefits of technology

It improves the conductivity and safety of electrolyte materials, improves ionic conductivity and cycling stability, reduces the formation of lithium dendrites, extends the service life of the battery and reduces the safety risks during use.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of a grinding aid for Sc / O doped sulfide solid electrolyte, which comprises the following steps: mixing and reacting ethanolamine thioglycolate, 2-vinyl-5, 5-dimethyl-1, 3, 2-borane dioxide, 1-allyl-3-ethylimidazolium hexafluorophosphate and potassium ethoxide in a solvent, reacting the ethanolamine thioglycolate with the 2-vinyl-5, 5-dimethyl-1, 3, 2-dioxo-borane, and reacting with the potassium ethoxide to obtain the grinding aid for Sc / O doped sulfide solid electrolyte. The grinding aid for the Sc / O doped sulfide solid electrolyte is prepared by the following steps: carrying out sulfydryl-alkenyl addition reaction on ethanol amine thioglycolate and 1, 2-borane dioxide, carrying out sulfydryl-alkenyl addition reaction on ethanol amine thioglycolate and 1-allyl-3-ethylimidazolium hexafluorophosphate, and removing a solvent after the reaction is finished, so as to obtain the grinding aid for the Sc / O doped sulfide solid electrolyte. The grinding aid can improve the microstructure of the electrolyte material, thereby enhancing the conductivity and safety of the electrolyte material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a method for preparing a grinding aid for Sc / O-doped sulfide solid electrolyte. Background Art

[0002] Sulfide solid electrolytes have become the best among many fast ion conductors due to their high ionic conductivity and excellent processability. 6 PS 5 Cl-type sulfide solid electrolytes are gradually becoming the main choice for the commercialization of sulfide solid-state batteries due to their relatively high ionic conductivity and price advantages. 6 PS 5 Cl-type sulfide solid electrolytes are extremely sensitive to moisture in the air and have poor interfacial compatibility with the negative electrode, which can easily lead to uneven lithium ion deposition and the formation of lithium dendrites at the interface. In severe cases, it can cause the failure of all-solid-state lithium metal batteries.

[0003] In order to improve the electrochemical performance of sulfide solid electrolytes, researchers have made many efforts. For example, the patent with publication number CN115051027A discloses a lithium argyrodite-type solid electrolyte containing an in-situ precipitation phase of lithium halide and a preparation method thereof. The electrolyte is obtained by doping a lithium argyrodite compound with a cation M, wherein the ionic radius of the cation M is greater than the ionic radius of phosphorus. The electrolyte induces cations M (specifically Al, Si, Sc, Y, Zr) with large ionic radius to occupy the P position through high-energy ball milling, realizes the doping of the P position, and forms a series of new cation M-doped lithium argyrodite sulfide electrolyte materials, thereby improving the uniform distribution of halogen X inside the grains and avoiding the formation of LiX coating layers on the grain surface; metastable halogen X atoms accompany Li atoms to precipitate LiX microparticles in situ, which are dispersed at the grain boundaries, greatly inhibiting the deposition and growth of metallic lithium inside the electrolyte, greatly improving the ability to inhibit lithium dendrites, and enabling all-solid-state batteries to operate at high current densities.

[0004] Reference (Zhao Zhengguang, Chen Zhenying, Zhai Guangqun, et al. Preparation of Sc / O doped sulfide solid electrolytes and performance of all-solid-state batteries [J]. Energy Storage Science and Technology, 2023, 12(8): 2412-2423.) discloses a series of modified sulfide solid electrolytes synthesized using rare earth element compound scandium oxide as a dopant. The results show that when the doping amount of scandium oxide is 0.04, Li 6.08 P 0.96 Sc 0.04 S 4.94 O 0.06 Cl sulfide solid electrolytes show high ionic conductivity, which can reach 3.17×10-3 S / cm, and even after being exposed to air for 90 min, the electrolyte still exhibits a good crystalline structure and good all-solid-state battery cycling performance.

[0005] But Li 6 PS 5 There is still room for improvement in the ionic conductivity, cycle stability and safety of Cl-type sulfide solid electrolytes. Summary of the invention

[0006] In order to solve the above problems existing in the prior art, the present invention provides a method for preparing a grinding aid for Sc / O-doped sulfide solid electrolyte, by which the microstructure of the electrolyte material can be improved, thereby improving the conductivity and safety of the electrolyte material.

[0007] To achieve the above object, according to one aspect of the present invention, a method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte is provided, the method comprising the following steps: adding thioglycolic acid ethanolamine (CAS: 126-97-6), 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane (CAS: 246869-22-7), 1-allyl-3-ethylimidazole hexafluorophosphate (CAS: 861908-19-2) and potassium ethoxide (CAS: 917-58-8) to a solvent for mixed reaction, and removing the solvent after the reaction is completed to obtain the grinding aid.

[0008] Reaction mechanism: Thioglycolic acid ethanolamine ester undergoes a thiol-alkenyl addition reaction with 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, and thioglycolic acid ethanolamine ester undergoes a thiol-alkenyl addition reaction with 1-allyl-3-ethylimidazole hexafluorophosphate, with potassium ethoxide as a catalyst.

[0009] Preferably, the mass ratio of thioglycolate ethanolamine, 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, 1-allyl-3-ethylimidazole hexafluorophosphate and potassium ethoxide is: 8.28-16.57: 0.75-3: 0.84-15.68: 1.68-4.21.

[0010] Preferably, the solvent is DMF (N,N-dimethylformamide), and more preferably, the ratio of DMF to ethanolamine thioglycolate is 100-200 ml: 8.28-16.57 g.

[0011] Preferably, the reaction temperature is 50-70°C, and the reaction time is 50-100 min.

[0012] Preferably, the method of removing the solvent is distillation.

[0013] To achieve the above object, according to another aspect of the present invention, a grinding aid for Sc / O-doped sulfide solid electrolyte prepared by the above preparation method is provided.

[0014] To achieve the above object, according to another aspect of the present invention, there is provided a method for preparing a Sc / O-doped sulfide solid electrolyte using the above-mentioned grinding aid, the method comprising the following steps: (1) Li 2 S.P. 2 S 5 , LiCl and Sc 2 O 3 Mixing evenly and ball milling to obtain powdered material; (2) The powdered material obtained in step (1) is pressed into a sheet, vacuum-sealed, and then subjected to a constant temperature heat treatment to obtain a sheet-like sulfide solid electrolyte material; (3) The flaky sulfide solid electrolyte material of step (2) is cooled to room temperature, and the Sc / O-doped sulfide solid electrolyte grinding aid is added thereto and ground into powder to obtain the Sc / O-doped sulfide solid electrolyte.

[0015] Preferably, in step (3), the added mass of the grinding aid for the Sc / O-doped sulfide solid electrolyte is 0.96%-4.3% of the mass of the sulfide solid electrolyte material.

[0016] Preferably, in step (1), Li 2 S.P. 2 S 5 , LiCl and Sc 2 O 3 The molar ratio is 2.5-2.6∶0.4-0.5∶1∶0.01-0.03, the ball milling speed is set to 500-600 r / min, and the ball milling time is set to 15-20 h.

[0017] Preferably, in step (2), the powdery material obtained in step (1) is pressed into a sheet material of 16-19 mm at a pressure of 500-800 Pa.

[0018] Preferably, in step (2), the process conditions of the isothermal heat treatment are: the heat treatment temperature is 500-600 °C, the heat treatment time is 5-10 h, and the heating and cooling rates are both 0.5 °C / min.

[0019] Preferably, in step (3), the grinding time is 10-20 min.

[0020] The beneficial effects of the present invention are as follows: (1) As a component of the grinding aid, the borane functional group can interact with the sulfide solid electrolyte material through its unique chemical properties, improve the crystallinity or microstructure of the material, thereby promoting ion transport and improving the ionic conductivity of the electrolyte; (2) 1-allyl-3-ethylimidazolium hexafluorophosphate can enhance ion mobility by providing additional charge carriers or changing the electronic structure of the material during the reaction, thereby improving the overall conductivity of the electrolyte material; (3) The use of 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane and 1-allyl-3-ethylimidazolium hexafluorophosphate not only helps to improve the charge and discharge efficiency of the battery, but also prolongs the battery life and reduces the safety risks during battery use. DETAILED DESCRIPTION

[0021] In order to further illustrate the technical means and effects adopted by the present invention, the specific implementation methods and effects of the present invention are described in detail below in combination with embodiments and comparative examples.

[0022] Example 1 A method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte is as follows: 8.28 g of ethanolamine thioglycolate, 0.75 g of 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, 0.84 g of 1-allyl-3-ethylimidazolium hexafluorophosphate and 1.68 g of potassium ethoxide were added to 100 ml of DMF, followed by stirring at 50° C. for 50 min, and DMF was distilled off to obtain a grinding aid.

[0023] The method for preparing Sc / O doped sulfide solid electrolyte using the above-mentioned grinding aid comprises the following steps: (1) Weigh 119.47 g Li in the glove box. 2 S, 111.13 g P 2 S 5 , 42.39 g LiCl and 4.14 g Sc 2 O 3 As the starting material, mix it evenly in the zirconia ball mill jar, then take the sealed zirconia ball mill jar out of the glove box and fix it on a high-energy planetary ball mill for ball milling. The ball milling speed is set to 600 r / min and the ball milling time is set to 20 h.

[0024] (2) After the ball milling is completed, the ball mill is placed back into the glove box, and the material is scraped off the wall of the zirconia ball mill to obtain a relatively uniform powder material. The obtained powder material is pressed into a 16 mm disc at a pressure of 500 Pa, and then vacuum-sealed into a quartz tube. The quartz tube is placed in a muffle furnace for constant temperature heat treatment. The process conditions for constant temperature heat treatment are: the heating and cooling rate is 0.5 ℃ / min, the heat treatment temperature is 600 ℃, and the heat treatment time is 10 h.

[0025] (3) After the temperature of the muffle furnace drops to room temperature, take out the quartz tube, take out the sheet material, i.e., the sulfide solid electrolyte material, from the quartz tube in the glove box, add 2.65 g of the above-mentioned grinding aid, and grind it with an agate mortar for 10 min. After the electrolyte material becomes powder, bottle it for later use.

[0026] Electrochemical performance test: The powdered sulfide solid electrolyte material obtained above was used to assemble a lithium-lithium symmetrical battery. 2 The lithium ion insertion / extraction cycle process was carried out at a critical current density (CCD) of 1.5 Å, with a stable operation time of 255 h.

[0027] Example 2 A method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte is as follows: 12.43 g of ethanolamine thioglycolate, 1.5 g of 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, 7.42 g of 1-allyl-3-ethylimidazolium hexafluorophosphate and 2.95 g of potassium ethoxide were added to 150 ml of DMF, followed by stirring at 60° C. for 75 min, and DMF was removed by distillation to obtain a grinding aid.

[0028] The method for preparing Sc / O doped sulfide solid electrolyte using the above-mentioned grinding aid comprises the following steps: (1) Weigh 116.7 g Li in the glove box. 2 S, 106.69 g P 2 S 5 , 42.39 g LiCl and 2.758 g Sc 2 O 3 As the starting material, mix it evenly in a zirconia ball mill jar, then take the sealed zirconia ball mill jar out of the glove box and fix it on a high-energy planetary ball mill for ball milling. The ball milling speed is set to 550 r / min and the ball milling time is set to 17 h.

[0029] (2) After the ball milling is completed, the ball mill is placed back into the glove box, and the material is scraped off the wall of the zirconia ball mill to obtain a relatively uniform powder material. The obtained powder material is pressed into an 18 mm disc at a pressure of 600 Pa, and then vacuum-sealed into a quartz tube. The quartz tube is placed in a muffle furnace for constant temperature heat treatment. The process conditions of the constant temperature heat treatment are: the heating and cooling rate is 0.5 ℃ / min, the heat treatment temperature is 550 ℃, and the heat treatment time is 7 h.

[0030] (3) After the temperature in the muffle furnace drops to room temperature, take out the quartz tube, take out the sheet material, i.e., the sulfide solid electrolyte material, from the quartz tube in the glove box, add 5.3 g of the above-mentioned grinding aid, and grind it with an agate mortar for 15 min. After the electrolyte material becomes powder, bottle it for later use.

[0031] Electrochemical performance test: The powdered sulfide solid electrolyte material obtained above was used to assemble a lithium-lithium symmetrical battery. 2 The lithium ion insertion / extraction cycle process was carried out at a critical current density (CCD) of 1.5 Å, with a stable operation time of 315 h.

[0032] Example 3 A method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte is as follows: 16.57 g of ethanolamine thioglycolate, 3 g of 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, 15.68 g of 1-allyl-3-ethylimidazole hexafluorophosphate and 4.21 g of potassium ethoxide were added to 200 ml of DMF, stirred at 70°C for 100 min, and DMF was distilled off to obtain a grinding aid.

[0033] The method for preparing Sc / O doped sulfide solid electrolyte using the above-mentioned grinding aid comprises the following steps: (1) Weigh 114.9 g Li in the glove box. 2 S, 88.9 g P 2 S 5 , 42.39 g LiCl and 1.379 g Sc 2 O 3 As the starting material, mix it evenly in a zirconia ball mill, then take the sealed zirconia ball mill out of the glove box and fix it on a high-energy planetary ball mill for ball milling. The ball milling speed is set to 500 r / min and the ball milling time is set to 15h.

[0034] (2) After the ball milling is completed, the ball mill is placed back into the glove box, and the material is scraped off the wall of the zirconia ball mill to obtain a relatively uniform powder material. The obtained powder material is pressed into a 19 mm disc at a pressure of 800 Pa, and then vacuum-sealed into a quartz tube. The quartz tube is placed in a muffle furnace for constant temperature heat treatment. The process conditions of the constant temperature heat treatment are: the heating and cooling rate is 0.5 ℃ / min, the heat treatment temperature is 500 ℃, and the heat treatment time is 5 h.

[0035] (3) After the temperature of the muffle furnace drops to room temperature, take out the quartz tube, take out the sheet material, i.e., the sulfide solid electrolyte material, from the quartz tube in the glove box, add 10.6 g of the above-mentioned grinding aid, and grind it with an agate mortar for 20 min. After the electrolyte material becomes powder, bottle it for later use.

[0036] Electrochemical performance test: The powdered sulfide solid electrolyte material obtained above was used to assemble a lithium-lithium symmetrical battery. 2 The lithium ion insertion / extraction cycle process was carried out at a critical current density (CCD) of 1.3 Å, with a stable operation time of 322 h.

[0037] Comparative Example 1 The difference between this comparative example and Example 1 is that in step (3) of preparing the Sc / O-doped sulfide solid electrolyte, no grinding aid is added, and the flaky sulfide solid electrolyte material is ground in an agate mortar for 15 min to obtain a powdered electrolyte material.

[0038] Electrochemical performance test: The obtained powdered sulfide solid electrolyte material was used to assemble a lithium-lithium symmetric battery, and the 2 The lithium ion insertion / extraction cycle process was carried out at a critical current density (CCD) of 1.5 Å, with a stable operation time of 100 h.

[0039] Comparative Example 2 The difference between this comparative example and Example 1 is that no ionic liquid is added to the grinding aid, and the rest is the same as Example 1.

[0040] A method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte is as follows: 12.43 g of ethanolamine thioglycolate, 1.5 g of 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane and 2.95 g of potassium ethoxide were added to 150 ml of DMF, followed by stirring at 60° C. for 75 min, and DMF was removed by distillation to obtain a grinding aid.

[0041] Electrochemical performance test: The powdered sulfide solid electrolyte material obtained above was used to assemble a lithium-lithium symmetrical battery. 2 The lithium ion insertion / extraction cycle process can be carried out at a critical current density (CCD) of 1.5 Å, and the stable operation time can be up to 224 h.

Claims

1. A method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte, characterized in that: include: Thioglycolic acid ethanolamine ester, 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, 1-allyl-3-ethylimidazolium hexafluorophosphate and potassium ethoxide are mixed and reacted in a solvent, and thioglycolic acid ethanolamine ester and 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane undergo a thiol-alkenyl addition reaction, and thioglycolic acid ethanolamine ester and 1-allyl-3-ethylimidazolium hexafluorophosphate undergo a thiol-alkenyl addition reaction. After the reaction is completed, the solvent is removed to obtain the grinding aid for the Sc / O doped sulfide solid electrolyte.

2. The method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte according to claim 1, characterized in that: The mass ratio of thioglycolate ethanolamine, 2-vinyl-5,5-dimethyl-1,3,2-dioxaborane, 1-allyl-3-ethylimidazole hexafluorophosphate and potassium ethoxide is: 8.28-16.57∶0.75-3∶0.84-15.68∶1.68-4.21。 3. The method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte according to claim 1, characterized in that: The solvent is DMF.

4. The method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte according to claim 1, characterized in that: The reaction temperature is 50-70 ℃, and the reaction time is 50-100 min.

5. The method for preparing a grinding aid for Sc / O doped sulfide solid electrolyte according to claim 1, characterized in that: The method for removing the solvent is distillation.

6. A grinding aid for Sc / O-doped sulfide solid electrolyte prepared by the preparation method according to any one of claims 1 to 5.

7. A method for preparing a Sc / O-doped sulfide solid electrolyte using the grinding aid for Sc / O-doped sulfide solid electrolyte according to claim 6, characterized in that: The following steps are involved: (1) Li2S, P2S5, LiCl and Sc2O3 are mixed evenly and ball-milled to obtain a powdery material; (2) The powdered material obtained in step (1) is pressed into a sheet, vacuum-sealed, and then subjected to a constant temperature heat treatment to obtain a sheet-like sulfide solid electrolyte material; (3) The flaky sulfide solid electrolyte material of step (2) is cooled to room temperature, and the Sc / O-doped sulfide solid electrolyte grinding aid is added thereto and ground into powder to obtain the Sc / O-doped sulfide solid electrolyte.

8. The method for preparing a Sc / O-doped sulfide solid electrolyte according to claim 7, characterized in that: In step (3), the added mass of the grinding aid for the Sc / O-doped sulfide solid electrolyte is 0.96%-4.3% of the mass of the Sc / O-doped sulfide solid electrolyte material.

9. The method for preparing Sc / O doped sulfide solid electrolyte according to claim 7, characterized in that: In step (1), the molar ratio of Li2S, P2S5, LiCl and Sc2O3 is 2.5-2.6:0.4-0.5:1:0.01-0.03, the ball milling speed is set to 500-600 r / min, and the ball milling time is set to 15-20 h.

10. The method for preparing Sc / O doped sulfide solid electrolyte according to claim 7, characterized in that: In step (2), the process conditions of the constant temperature heat treatment are: the heat treatment temperature is 500-600 °C, the heat treatment time is 5-10 h, and the heating and cooling rates are both 0.5 °C / min.

Citation Information

Patent Citations

  • Lithium argyrodite type solid electrolyte containing lithium halide in-situ precipitated phase as well as preparation method and application of lithium argyrodite type solid electrolyte

    CN115051027A

  • Preparation method of compound with optical activity

    CN102050820A

  • Polymer solid-state electrolyte material and preparation method therefor

    CN107069081A

  • Sulfide-polymer composite solid electrolyte membrane prepared through molecular hybridization and preparation method and application thereof

    CN116284740A

  • Flame resistant quasi-solid and solid electrolyte for lithium ion and lithium metal batteries and method of production

    CN116964808A

Cited By

  • A Li 10+3x SnP 2-x Zn x S 12-x O x Preparation method of sulfide solid-state battery

    CN122716408A